2008
DOI: 10.2486/indhealth.46.541
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Mortality of Young, Middle-aged and Elderly Males and Females in Japan for the Years 1953-96: Time Series Analysis for the Effects of Unemployment, Female Labour Force, Young and Aged Population, Primary Industry and Population Density

Abstract: Effects of nine social life indicators on age-adjusted and age-specific annual suicide mortality of male and female Japanese population in the years 1953-96 were investigated by multiple regression analysis on time series data. Unemployment rate was significantly related to the age-adjusted mortality in both males and females. Also, female labour force participation was positively related to the male mortality; persons and 65 and above was inversely related to the male mortality. Results on the age-specific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
2
22
2
Order By: Relevance
“…Previous study revealed that the relations between suicide mortality rate and socioeconomic factors varied not only in gender (Andrés et al, 2010) but also in age, periods and localities (Aihara et al, 2002;Yamasaki et al, 2008). These prompted us to make further analyses on Japanese suicide by age and region (e.g., at the national level or the prefecture level).…”
Section: Discussionmentioning
confidence: 97%
“…Previous study revealed that the relations between suicide mortality rate and socioeconomic factors varied not only in gender (Andrés et al, 2010) but also in age, periods and localities (Aihara et al, 2002;Yamasaki et al, 2008). These prompted us to make further analyses on Japanese suicide by age and region (e.g., at the national level or the prefecture level).…”
Section: Discussionmentioning
confidence: 97%
“…A study with recent Taiwan data observed that never married males had the highest suicide rates [39]. Divorce was also related to suicides in Japan [40], Taiwan [41], Australia [42] and Romania [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Some other studies report a mixed or changing relationship between FLFP and suicide (Burr, McCall, & PowellGriner, 1997;Lucey et al, 2005;Stack, 1987;Trovato & Vos, 1992), which may be because social norms and values have adjusted to female employment in high-income countries over time (i.e., as female employment does not pose a threat to normative values or roles in society) (Austin, Bologna, & Hayama Dodge, 1992;Stack, 2000b). However, other research supports the idea that female participation in the workforce has an adverse influence on male and female suicide rates (Aliverdinia & Pridemore, 2009;Cutright & Fernquist, 2001a;Fernquist, 1999;Fernquist & Cutright, 1998;Milner, McClure, et al, 2012;Neumayer, 2003;Yamasaki, Araki, Sakai, & Voorhees, 2008). Some of the reasons for these differences may be connected to social, economic or cultural differences in the settings under study.…”
Section: Female Participation In the Workforce (N = 18)mentioning
confidence: 98%